Effect of Nonnutritive Sucking and Oral Stimulation on Feeding Performance in Preterm Infants: A Randomized Controlled Trial - Zhang, Y.; Lyu, T.; Hu, X.; Shi, P.; Cao, Y.; Latour, Jos (Lippincott Williams & Wilkins, 2014)
Objectives: To evaluate the effectiveness of nonnutritive sucking (NNS) and oral stimulation (OS), either applied alone or in combination, to reduce the transition time from tube feeding to independent oral feeding. Design: Randomized controlled trial. Setting: A 40-bed neonatal ICU in a university hospital in the People’s Republic of China. Patients: A total of 120 preterm infants were admitted to the neonatal ICU from December 2012 to July 2013. Interventions: Oral motor interventions. Measurements and Main Results: One hundred twelve preterm infants were assigned to three intervention groups (NNS, OS, and combined NNS + OS) and one control group. Primary outcome was the number of days needed from introduction of oral feeding to autonomous oral feeding (transition time). Secondary outcome measures were the rate of milk transfer (mL/min), proficiency (intake first 5 min/volume ordered), volume transfer (volume transferred during entire feeding/volume prescribed), weight, and hospital length of stay. Transition time was reduced in the three intervention groups compared with the control group (p < 0.001). The milk transfer rate in the three intervention groups was greater than in the control group (F3,363 = 15.37; p < 0.001). Proficiency in the NNS and OS groups did not exceed that in the control group while the proficiency in the NNS + OS group was greater than that in the control group at the stage when the infants initiated the oral feeding (p = 0.035). Among all groups, no significant difference was found on weight gain and length of stay. Conclusions: The combined NNS + OS intervention reduced the transition time from introduction to independent oral feeding and enhanced the milk transfer rate. The combined intervention seems to have a beneficial effect on oral feeding proficiency in preterm infants.